State information policy in modern society - Temeshov Temirlan Berikovich; Onuchko Marina Yurievna (World Scientific Reports, 2023)
Global media space is gradually moving to the Internet, fundamentally changing the level and nature of communication processes, as well as the modern person’s view of published news. Today, almost every media outlet has its own official websites and pages on social networks. Electronic newspapers, magazines, television and radio, which work online, have created a new kind of activity - online journalism. The history of online media is a major part of journalism. The Internet has opened up a lot of opportunities for the media and developed a new way to disseminate information to a wide audience quickly and with high quality. There has been a convergence of genres, which has created new forms of presentation. The famous American linguist Noam Chomsky argued that information is modern oil, and one of the most successful bankers in the world, the creator of the giant family-banking corporation Nathan Rothschild once remarked that “who owns information, he owns the world”. In just one generation, the Internet has changed the way news is presented and perceived by audiences. Today it is hard for people to imagine their lives without the Internet. Every day every user of World Wide Web several times a day opens the news portals to get acquainted with the current information picture of the day. This is evidenced by the trends on the media market. Analysis of consumer demand shows that the Internet, television and newspapers are the most popular media. There is a pronounced tendency to expand the use of online media. Exploring new channels of communication and content distribution, print media are losing the audience for their paper versions, but are significantly expanding their overall audience at the expense of the online segment.